Measuring first use of force: methods, results, and implications. (2nd January 2019) - Brown, Davis
ABSTRACT: Why do states violate jus ad bellum and how do we know? Lack of comprehensive data on armed conflict initiation, as opposed to occurrence, hampers scholarly understanding of this question. Datasets used by political scientists do not measure the critical legal outcome – violation of Article 2(4). In response, this article derives such a variable from the Militarised Interstate Disputes (MID) dataset, at progressively higher thresholds of severity of militarisation. This enables empirical testing for relationships of other political characteristics on low-, mid-, and high-level interstate armed conflict initiation. This article illustrates this variable's prospective applications by regressing initiation of interstate armed conflict on many other armed conflict contributors grounded in the international relations literature, including regime type, power, wealth, alliances, proximity, trade dependence, unilateralism, and time. Results show which factors are related most consistently to Article 2(4) violations – autocracy, proximity, and recency of past conflict – and which factors are not.